Response of Sorghum [Sorghum bicolor(L.) Moench] to Phosphorus and Nitrogen Fertilization under Rainfed Conditions, Blue Nile State – Sudan* (University of Khartoum Journal of Agricultural Sciences, 2023)
Two field experiments were conducted on a Typicchromusterts, fine, smectitic, isohyperthermic soil series in the DamazinResearch Station farm during two seasons (2005/06 and 2006/07). Theobjective was to investigate the effect of phosphorus (P) and nitrogen (N)and their interactions on sorghum [Sorghum bicolor (L.) Moench] growthand grain yield. A randomized complete block design with four replicateswas used to execute the experiments. Plant height, grain yield and drymatter were significantly increased by N and P applications, in bothseasons.The average yield of sorghum grain in the two seasons was 0.6tons ha-1 for the control and 4.4 tons ha-1 for the highest fertilizer treatment(P 80 N80 ). There were mutually synergistic effects between N and P whichsignificantly (P
Keywords: Rainfed sorghum; phosphorus; nitrogen; Blue Nile State; Sudan